Architectural Criteria for PV Integration in Heritage Landscape - Sandoval, L. (37th European Photovoltaic Solar Energy Conference and Exhibition, 2020)
(Poster presentation and explanatory video on virtual Event Platform) It is proposed to evaluate the benefit of an integrated model in the management of photovoltaic energy applied in traditional villages. In projects related to vernacular architecture, the installation and use of photovoltaic (PV) panels generate significant formal conflicts in the traditional landscape, since they become alien to its heritage, which is characterized by using local materials and construction techniques sustainable. The research assumes that it is possible to integrate photovoltaic energy into heritage architecture without changing the vernacular language in the cultural landscape. To achieve the above, the available solar technologies and the vernacular architecture values will be analyzed to propose and validate with interdisciplinary criteria, in the context of the increased use in energy efficiency in the architectural heritage.